Hemodynamic effects of cycle ergometer in critical cancer patients: relation length of stay and type of treatment - Lins, Wylisson Marcelo Almeida; Leão, Ana Cristina Machado; Bergmann, Anke (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: In recent years, with the implementation of new chemotherapy protocols, radiation and surgery, there was an improvement in cancer patient’s prognosis. However, both the treatment and the disease itself generate a series of complications, worsening clinical condition, which may lead to the need for admission to the intensive care unit (ICU). Physical therapy works on physical and functional recovery of these individuals, using manual and / or mechanical features, among them the cycle ergometer is gaining prominence, but there is in the literature any study evaluating the use of this technique in critical cancer patients. Objective: To evaluate the influence length of stay and type of treatment on hemodynamic behavior in response to an active cycle ergometer in cancer patients in intensive care. Methods: We performed a single active intervention cycle ergometer lower limb (no load) for 10 minutes. The variables included heart rate and mean arterial blood pressure and systolic blood pressure, which were evaluated in four stages: rest, 5 and10 minutes of activity and 10 minutes of recovery. Data on the patient and his or her medical history were previously obtained from their medical records. Results: The study included 23 patients, most were males; under the age of 65; hospital stays shorter than 14 days. It was observed that elderly patients, females, patients with a long hospital stay greater than 14 days, and patients in a clinical hospital showed higher variations in heart rate, mean arterial blood pressure and systolic blood pressure during the entire activity. Conclusion: The results of this study indicate that no individual had clinical complications during exercise. Hemodynamic changes occurred more frequently in the group of elderly patients, clinical and longer hospital stays.